Словообразовательные процессы в русском сленге (на примере наименований лиц) - Wilk, Gabriela (Studia Rossica Posnaniensia, 2015)
This paper is devoted to studying productive word formation processes in Russian slang (creating new words morphologically and semantic derivation). The paper focuses on terms which are used to name people and which were taken from S.I. Levikova’s The Great Dictionary of Youth Slang. The lexical units that are analyzed are not stylistically neutral, and their expressiveness can be achieved through suffixation, compounding, contamination, clipping or via metaphors and metonymies.